Comparing ChatGPT-3.5 and ChatGPT-4’s alignments with the German evidence-based S3 guideline for adult soft tissue sarcoma - Li, Cheng-Peng; Jakob, Jens; Menge, Franka; Reißfelder, Christoph; Hohenberger, Peter; Yang, Cui (iScience, 2024)
Clinical reliability assessment of large language models is necessary due to their increasing use in healthcare. This study assessed the performance of ChatGPT-3.5 and ChatGPT-4 in answering questions deducted from the German evidence-based S3 guideline for adult soft tissue sarcoma (STS). Reponses to 80 complex clinical questions covering diagnosis, treatment, and surveillance aspects were independently scored by two sarcoma experts for accuracy and adequacy. ChatGPT-4 outperformed ChatGPT-3.5 overall, with higher median scores in both accuracy (5.5 vs. 5.0) and adequacy (5.0 vs. 4.0). While both versions performed similarly on questions about retroperitoneal/visceral sarcoma and gastrointestinal stromal tumor (GIST)-specific treatment as well as questions about surveillance, ChatGPT-4 performed better on questions about general STS treatment and extremity/trunk sarcomas. Despite their potential as a supportive tool, both models occasionally offered misleading and potentially life-threatening information. This underscores the significance of cautious adoption and human monitoring in clinical settings.